UNEMPLOYMENT – THE UNBALANCE OF THE LABOUR MARKET IN JIU VALLEY - OANA DOBRE-BARON; ALINA FLEŞER (Annals of the University of Petrosani: Economics)
During several decades, Jiu Valley has represented one of the labour markets, which, like a sponge, absorbed labour force from all over the country. As the number of the population increased the number of the population working in the mine industry became the highest in the country. But everything came to a stop in the year 1997, year representing the great layoff in Jiu Valley. The paper will deal with the labour market and unemployment in this mono-industrial area, as a result of the decisions to reorganise the mining industry.